Massive and Microscopic Sensemaking During COVID-19 Times. (September 2021) - Markham, Annette N.; Harris, Anne; Luka, Mary Elizabeth
How does this pandemic moment help us to think about the relationships between self and other, or between humans and the planet? How are people making sense of COVID-19 in their everyday lives, both as a local and intimate occurrence with microscopic properties, and a planetary-scale event with potentially massive outcomes? In this paper we describe our approach to a large-scale, still-ongoing experiment involving more than 150 people from 26 countries. Grounded in autoethnography practice and critical pedagogy, we offered 21 days of self guided prompts to for us and the other participants to explore their own lived experience. Our project illustrates the power of applying a feminist perspective and an ethic of care to engage in open ended collaboration during times of globally-felt trauma.